Cardiovascular Magnetic Resonance as Pathophysiologic Tool in Diabetes Mellitus - Mavrogeni, Sophie I.; Bacopoulou, Flora; Markousis-Mavrogenis, George; Giannakopoulou, Aikaterini; Kariki, Ourania; Vartela, Vasiliki; Kolovou, Genovefa; Charmandari, Evangelia; Chrousos, George (Frontiers in Endocrinology, 2021)
Diabetes mellitus can independently contribute to cardiovascular disease and represents a severe risk factor for premature development of cardiovascular disease. A three-fold higher mortality than the general population has been observed in type 1 diabetes mellitus whereas a 2- to 4-fold increased probability to develop cardiovascular disease has been observed in type 2 diabetes mellitus. Cardiovascular magnetic resonance, a non-radiative modality, is superior to all other modalities in detecting myocardial infarction. The main cardiovascular magnetic resonance sequences used include a) balanced steady-state free precession (bSSFP) for function evaluation; b) T2-W for oedema detection; c) T1 W for ischemia detection during adenosine stress; and d) late gadolinium enhanced T1-W images (LGE), evaluated 15 min after injection of paramagnetic contrast agent gadolinium, that permit the diagnosis of replacement fibrosis, which appears white in the middle of suppressed, nulled myocardium. Although LGE is the technique of choice for diagnosis of replacement fibrosis, it cannot assess diffuse myocardial fibrosis. The application of T1 mapping (native or pre contrast and post contrast) allows identification of diffuse myocardial fibrosis, which is not detectable my other means. Native T1 and Contrast-enhanced T1 mapping are involved in the extracellular volume fraction (ECV) calculation. Recently, 1H-Cardiovascular magnetic resonance spectroscopy has been applied to calculate the amount of myocardial triglycerides, but at the moment it is not part of the routine assessment of diabetes mellitus. The multifaceted nature of cardiovascular magnetic resonance has the great potential of concurrent evaluation of function and myocardial ischemia/fibrosis in the same examination and represents an indispensable tool for accurate diagnosis of cardiovascular disease in diabetes mellitus.